DESKRIPSI TINGKAT KECEMASAN REMAJA PUTRI YANG MENGALAMI MENARCH DI SMP ISLAM TERPADU KHOLISATURRAHMI BINJAI - Leny Suarni (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
Menarche is the first menstruation that usually occurs in the age range of 10-16 years or in early adolescence in the middle of puberty before entering reproduction (Proverawati and Misaroh, 2009). Menarche is the first mestruasi blood expenditure, the arrival of menarche can cause positive or negative reactions, a positive reaction if the individual is able to appreciate, understand and accept menarche as a sign of maturity that is owned by a woman otherwise a negative reaction will cause anxiety. Anxiety is a condition where an individual or group experiences anxiety (judgment or opinion) and autonomic nervous system activity in responding to threats that are unclear, non specific. The purpose of this research is to determine the level of anxiety of adolescents facing menarche in IT Khalisaturrahmi Binjai, mild anxiety level, moderate anxiety level, severe anxiety level. The type of research used is descriptive. The population in this study amounted to 32 respondents. The sample in this study amounted to 24 respondents with consecutive sampling techniques. The results showed that respondents experienced mild anxiety levels of 12 people (50%), 8 people (33%) moderate anxiety and 4 people (17%) with severe anxiety. From the results of the study it can be concluded that the level of anxiety of adolescents facing menarche in IT Middle School Khalisaturrahmi Binjai majority in the category of mild anxiety levels, amounting to 12 respondents or (50%). Further researchers are advised to conduct research on the handling of anxiety in young women in the face of menarche. Keywords: Anxiety, Princess Adolescents, Menarche